From local to global: a framework to monitor river health - Tickner, David; Kuehne, Lauren; Lynch, Abby; Sadiki, Mpho; Dickens, Chris (CGIAR, 2024)
River health is declining globally, but there is no reliable basis for tracking global trends. NEXUS Gains therefore reviewed national and regional approaches for river health monitoring to develop a comprehensive set of scalable indicators that can support “top-down” global surveillance while also facilitating standardized “bottom-up” local monitoring efforts. This webinar evaluates the readiness of these indicators for implementation at a global scale; charts a road map that identifies data and technical priorities and opportunities to advance global river health monitoring by 2030; and presents recommendations for coordinated action and investment by policy makers, research funders, and scientists to develop and implement a framework to support conservation and restoration of river health globally